1976
DOI: 10.1111/j.2044-8260.1976.tb00020.x
|View full text |Cite
|
Sign up to set email alerts
|

Choice Reaction Times in Depressive States

Abstract: An experiment was performed in which two components of response latency, decision time (DT) and movement time (MT), were measured in two relatively homogeneous samples of neurotic and psychotic depressive patients, together with a normal control group. It was found that whereas both DT and MT were significantly longer in the depressive samples than in the control sample, only DT was significantly longer in the psychotic than in the neurotic depressive sample. Thus while both DT and MT were elevated among the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1
1

Year Published

1980
1980
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 11 publications
(22 reference statements)
1
17
1
1
Order By: Relevance
“…Consequently, we prefer to tentatively view the results as indicating that a depressed mood may be associated with slower perceptual processing. Such a conclusion would be supported by some research with other paradigms on clinically depressed samples (e.g., Byrne, 1976;Payne & Hewlett, 1960).…”
Section: Discussionmentioning
confidence: 68%
“…Consequently, we prefer to tentatively view the results as indicating that a depressed mood may be associated with slower perceptual processing. Such a conclusion would be supported by some research with other paradigms on clinically depressed samples (e.g., Byrne, 1976;Payne & Hewlett, 1960).…”
Section: Discussionmentioning
confidence: 68%
“…Cognitive slowing in depression is the psychological counterpart of motor slowing, which accompanies depression. Some authors [e.g., Byrne, 1976] showed that this slowing affects as much the central aspect (decision making) as the peripheral aspect (motor aspect) of RT. While control subjects produced stable performances from one session to another, there was a significant improvement in RTs for depressed subjects after the first 3 weeks of treatment, which indicated improvement in psychomotor slowing under antidepressant treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Second, Mogg et al assessed comprehension latencies for entire sentences, which increases variability in reaction times. This high variability, compounded by the fact that depressed individuals tend to exhibit variable reaction times in general (Byrne 1976), may have attenuated group differences in response latencies. In contrast, the text stimuli used in the present study were explicitly self-referential, and latencies used to examine group differences were in response to a single word that completed each three-sentence story, thus reducing variability in reaction times.…”
Section: Discussionmentioning
confidence: 99%